Extracorporeal Membrane Oxygenation in Immunocompromised Patients With Acute Respiratory Distress Syndrome—A Retrospective Cohort Study - Cheng, Chiao-Feng; Chen, You-Yi; Shih, Ming-Chieh; Huang, Yi-Min; Tseng, Li-Jung; Lai, Chien-Heng; Lan, Ting-Yuan; Lu, Cheng-Hsun; Hsieh, Song-Chou; Li, Ko-Jen; Chi, Nai-Hsin; Yu, Hsi-Yu; et al. (Frontiers in Medicine, 2021)
Objective: Although the negative impact of immunosuppression on survival in patients with acute respiratory distress syndrome (ARDS) treated by extracorporeal membrane oxygenation (ECMO) is well known, short-term outcomes such as successful weaning rate from ECMO and subgroups benefit most from ECMO remain to be determined. The aims of this study were (1) to identify the association between immunocompromised status and weaning from ECMO in patients of ARDS, and (2) to identify subgroups of immunocompromised patients who may benefit from ECMO. Methods: This retrospective cohort study enrolled patients who received ECMO for ARDS from 2010 to 2020. Immunocompromised status was defined as having a hematological malignancy, active solid tumor, solid organ transplant, or autoimmune disease. Results: This study enrolled 256 ARDS patients who received ECMO, of whom 68 were immunocompromised. The multivariable analysis showed that immunocompromised status was not independently associated with failure to wean from ECMO. In addition, the patients with an autoimmune disease (14/24, 58.3%) and organ transplantation (3/3, 100%) had a numerically higher weaning rate from ECMO than other immunocompromised patients. For causes of ARDS, most patients with pulmonary hemorrhage (6/8, 75%) and aspiration (5/9, 55.6%) could be weaned from ECMO, compared to only a few of the patients with interstitial lung disease (2/9, 22.2%) and sepsis (1/4, 25%). Conclusions: Immunocompromised status was not an independent risk factor of failure to wean from ECMO in patients with ARDS. For patients with pulmonary hemorrhage and aspiration-related ARDS, ECMO may be beneficial as bridge therapy.